Miles Morales : Shock Waves - Reynolds, Justin A.; Leon, Pablo; Geoffo; Maher, Ariana (New York, NY : Graphix, an imprint of Scholastic, 2021)
Miles Morales, Brooklyns Spider-Man, learns that the disappearance of a new students father is linked to the giant corporation sponsoring Miles fundraiser for the victims of the Puerto Rico earthquake and sets out to discover the truth
Keywords: Spider-Man -- (Fictitious character) -- Comic books, strips, etc; Spider-Man -- (Fictitious character) -- Juvenile fiction; Morales, Miles -- (Fictitious character) -- Comic books, strips, etc; Morales, Miles -- (Fictitious character) -- Juvenile fiction; Superheroes -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Missing persons -- Comic books, strips, etc; Teenage boys -- Comic books, strips, etc; Racially mixed youth -- Comic books, strips, etc; Superheroes -- Juvenile fiction; Good and evil -- Juvenile fiction; Missing persons -- Juvenile fiction; Teenage boys -- Juvenile fiction; Racially mixed youth -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Comic books, strips, etc; Brooklyn (New York, N.Y.) -- Juvenile fiction; Graphic novels; superhero comics; adventure story comics; Science fiction comics; Humorous comics; Action and adventure comics; Action and adventure fiction; Comics (Graphic works); Fiction; Graphic novels; Juvenile works; Superhero comics; Superhero fiction; Childrens stories -- Comic books, strips, etc; Superhero comics; Superhero fiction; Science fiction comics; Action and adventure comics; Action and adventure fiction; Comics (Graphic works); Humorous comics